Rhopalopsole magnispina sp. nov., a new species of Leuctridae (Plecoptera) from China, with notes on R. horvati Sivec & Harper, 2008 - Li, Wenliang; Zhang, Yao; Yang, Ding; Li, Weihai (Zootaxa, 2022)
Rhopalosole magnispina sp. nov., a new species of R. shaanxiensis Yang & Yang, 1994 species Group of stonefly family Leuctridae is described, illustrated, and compared with related taxa. The female of R. horvati Sivec & Harper, 2008 is associated based on mating pairs collected in the Qinling Mountains of Shaanxi Province. The original female of R. horvati was erroneously associated and considered herein as an unidentified Rhopalosole female of the R. shaanxiensis Group.